Implementasi Riset Aksi Sebagai Desain Penelitian pada Masyarakat dan Imu Ekonomi - mujhirul, iman (Pascasarjana Universitas Islam Negeri Sumatera Utara Medan, 2024)
The purpose of this study is to determine the implementation of action research as one of the research designs in society. This study uses a type of qualitative research with a literature study approach. The data sources come from primary and secondary data, namely sources of reading materials, in the form of personal letters, official documents, books, research results in the form of reports, and so on. The data collection technique is carried out with data reduction techniques. Collect all the data obtained through literature and conclude it as a result of research. The results of the study show that One of the applied, pragmatic, and integrative research techniques that must be created and used by academic institutions is Research Action. This is done in an effort to overcome actual issues that arise in society. Action research also helps in increasing the relevance of the tridharma activities of higher education in relation to actual issues facing society, ensuring that universities are more than just scientific ivory towers and that their presence is felt by society. Therefore, society considers universities as actual entities that are the subject of action research and actively contribute to the creation of a rich society, as desired by science itself, especially economics.